2021
DOI: 10.1111/bdi.13172
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of bipolar disorders and body mass index predict clustering based on similarities in cortical thickness—ENIGMA study in 2436 individuals

Abstract: Aims: Rates of obesity have reached epidemic proportions, especially among people with psychiatric disorders. While the effects of obesity on the brain are of major interest in medicine, they remain markedly under-researched in psychiatry. Methods:We obtained body mass index (BMI) and magnetic resonance imagingderived regional cortical thickness, surface area from 836 bipolar disorders (BD) and 1600 control individuals from 14 sites within the ENIGMA-BD Working Group. We identified regionally specific profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
(137 reference statements)
2
13
0
Order By: Relevance
“…The ENIGMA-BD Working Group aims to improve replication and generalizability of neuroimaging studies of BD by combining existing, independently collected neuroimaging samples of BD from around the world (Ching et al, 2022;Hibar et al, 2018Hibar et al, , 2016McWhinney et al, 2021aMcWhinney et al, , 2022aNunes et al, 2020). Seventeen independently collected ENIGMA-BD samples from 13 countries on six continents contributed individual-level structural MRI data, medication information, specifically medications used at the time of scanning for the following medication categories (lithium, first-, second-generation antipsychotics, anticonvulsants, antidepressants), and body mass index (BMI) values from a total of 1231 individuals with BD and 1601 healthy controls.…”
Section: Participating Sitesmentioning
confidence: 99%
“…The ENIGMA-BD Working Group aims to improve replication and generalizability of neuroimaging studies of BD by combining existing, independently collected neuroimaging samples of BD from around the world (Ching et al, 2022;Hibar et al, 2018Hibar et al, , 2016McWhinney et al, 2021aMcWhinney et al, , 2022aNunes et al, 2020). Seventeen independently collected ENIGMA-BD samples from 13 countries on six continents contributed individual-level structural MRI data, medication information, specifically medications used at the time of scanning for the following medication categories (lithium, first-, second-generation antipsychotics, anticonvulsants, antidepressants), and body mass index (BMI) values from a total of 1231 individuals with BD and 1601 healthy controls.…”
Section: Participating Sitesmentioning
confidence: 99%
“…We found that there were no strictly separate clusters in brain imaging data and that the boundaries between BD and controls were not clear, i.e. many controls fell into the cluster together with BD individuals, while some BD individuals clustered with controls (McWhinney, Abé, et al, 2022 ). The cluster assignment of individuals in part depended on continuous variables including age and BMI and effectively resulted in categorizing of these continuous variables, which is not optimal.…”
Section: Introductionmentioning
confidence: 84%
“…It is increasingly clear that brain alterations in severe mental illnesses (SMI) are multifactorial. Aside from the diagnosis, they also reflect the effects of additional clinical factors, including medications (Hajek et al, 2012 ; McWhinney, Abé, et al, 2022 ; Van Gestel et al, 2019 ), and comorbid psychiatric or physical conditions, such as obesity (McWhinney, Abé, et al, 2021 ; McWhinney, Brosch, et al, 2022 ; McWhinney, Kolenic, et al, 2021 ) and diabetes (Hajek et al, 2014 , 2016 ). Understanding the brain changes in SMI and translating these findings into clinical settings requires sensitive and replicable methods that link patterns of brain alterations to system‐level variables.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that obesity is a risk factor for mood disorders and vice versa [50][51][52]. In addition, obesity is consistently associated with cognitive impairment [53] and neurostructural alterations [54][55][56][57]. There is some evidence suggesting that weight loss may improve brain structure [58] which could also positively impact cognitive functions [59] and/or psychiatric symptoms [60].…”
Section: Discussionmentioning
confidence: 99%